Предмет: Математика,
автор: tatuchka
ln(sqrt((e^(2x))+(e^(-2x))))
Ответы
Автор ответа:
0
e^(2x) + e^(-2x) = e^2x + 1/e ^ (2x) = (e^4x + 1)/e^2x Это выражение стоит под корнем. Из знаменателя корень извлекается.
ln √(e^4x +1)/e^x = ln √(e^4x +1) - ln e^x = 1/2ln(e^4x + 1) -x
ln √(e^4x +1)/e^x = ln √(e^4x +1) - ln e^x = 1/2ln(e^4x + 1) -x
Похожие вопросы
Предмет: Химия,
автор: kiunetosr
Предмет: История,
автор: Аноним
Предмет: Русский язык,
автор: demina1236
Предмет: Математика,
автор: braganb
Предмет: Математика,
автор: horocho2002